ANALISA SETTING GROUND FAULT RELAY (GFR) TERHADAP SISTEM PENTANAHAN NETRAL PENYULANG PANDEANLAMPER 06 JTM 20 KV SEMARANG - Muhammad Iqbal; Moh Toni Prasetyo; Luqman Assaffat (PSTE UNIMUS, 2016)
The operation of the distribution system has major problems in overcoming interference. In its development, electric power systems increasingly large currents cause electrical interference that may occur the greater. Therefore, they invented a system called neutral grounding.There is no ideal grounding neutral earthing throughout the distribution network Semarang cause neutral grounding resistance value. Neutral resistance values may cause a decrease in current flowing to ground disturbance that affects the sensitivity GFR (Ground Foult Relay) installed. Because of that, necessary to analyze the GFR setting the main feeder neutral earthing systems JTM 20 kV feeders Semarang bytaking samples Pandealamper 06 to determine the condition of setting GFR installed in accordance with the neutral earthing systems.Results of the calculation of the noise current by entering the value of resistance neutral earthing exiting GFR values obtained ideal setting on the feeder Pandeanlamper06 is not much different from the existing GFR setting value. Values of 0.27 ? neutral earthing (existing) did not significantly influence the sensitivity GFR of the feeder PDL 06.GFR remaineddetect interference and work in accordance with the characteristic curve GFR.Based on the analysis, GFR mounted setting was appropriate and able to provide security in Pandeanlamper feeder 06.Keywords: Neutral Grounding, GFR, Main Feeder